Evaluating the Sustainability Performance of Typical Conventional and Certified Coffee Production Systems in Brazil and Ethiopia Based on Expert Judgements - Winter, Eva; Marton, Silvia M. R. R.; Baumgart, Lukas; Curran, Michael; Stolze, Matthias; Schader, Christian (Frontiers in Sustainable Food Systems, 2020)
Increasing consumer awareness on sustainability issues has led to the growing adoption of voluntary sustainability standards in agriculture. This study assesses the sustainability performance of typical conventional and certified coffee production systems in Brazil and Ethiopia based on expert judgements. We apply the SMART-Farm Tool, which represents an operationalization of the SAFA (Sustainability Assessment of Food and Agriculture systems) framework of FAO. Data were collected through expert interviews and uncertainties were estimated using Monte-Carlo simulations. A higher sustainability performance of the certified systems was observed regarding product information (+37%) and transparency (+39%) in Ethiopia. In Brazil, the certified system showed a higher overall sustainability performance compared to the conventional system in the environmental dimension and in some social and governance aspects, e.g., gender equality (+49%) and public health (+36%). Geographical or political conditions and farm type also had a strong influence on the observed sustainability performance. Typical smallholder production systems in Ethiopian coffee production performed comparable in the environmental dimension since all were low-input systems due to economic constraints. The conventional Brazilian system showed a better performance concerning employment relations (+14%) and profitability (+13%), as compared to the certified Brazilian systems, because larger farms were more likely to employ permanent staff and benefit from economies of scale.